Design of enterprise architecture for Yayasan Kemala Bhayangkari Indonesia Institute using TOGAF - Lione Putri Misani; Riyanto Jayadi (Institute of Computer Science (IOCS), 2022)
The World Health Organization has declared Covid-19 as a pandemic that has posed a contemporary threat to humanity. This pandemic has successfully forced global shutdown of several activities, including education activities. In this case, educational institutions also received some consequences like decreasing the number of students. This happed to Yayasan Kemala Bhayangkari (YKB) Indonesia, a government educational foundation which has more than 700 schools spread all over Indonesia face decreasing student year by year. This foundation is under bhayangkari’s management. Bhayangkari is an organization that is managed by POLRI’s wives. We see the schools where is out of Jawa Island, loss the students more than 50% due to covid-19 pandemic. Therefore, the design of Institution business architecture is needed to align business processes. This study begins with data collection by conducting interviews, observations, and literature studies, then performs an analysis using the TOGAF 9.1 framework. The results of this research, in the form of a blueprint which is a proposed application for Institution, it is hoped that the proposed applications can help this foundation in aligning business processes well and can achieve business goals. The conclusion of this research is that architectural design using the TOGAF 9.1 method can harmonize the business process activities of this foundation.